Altitudinal distribution of ants (Hymenoptera, Formicidae) in the northwest slope of the Sierra Nevada de Santa Marta (Colombia). - Guerrero, Roberto J.; Sarmiento, Carlos E. (Instituto de Ecología, A.C., 2010)
The composition and altitudinal distribution of ants along the northwestern slope of the Sierra Nevada de Santa Marta is described. A total of 40 genera and 136 species were collected; Myrmicinae was the richest subfamily at the generic and specific levels at all altitudes. Total ant richness and epigaeic ant richness decreases with altitude while the richness of litter ants was higher at intermediate altitudes. Despite the high level of species turnover along the altitude gradient, the dominance of taxa with low abundance at all altitudes suggests similar ecological elements along the gradient but especially in the three higher altitudes. On the other hand, species turnover, abundancebased similarity, and incidence-based similarity suggest that ant fauna is divided into two major groups along the gradient, the first one is between 835 and 968 masl, and the second group is found between 1198 and 1395 masl. Ant fauna composition and distribution along the northwestern slope could be explained by Rapoport’s rule and the mid-domain effect.